Medium-strength high-plasticity Ti-Ta alloy resistant to corrosion of boiling concentrated nitric acid and preparation method of medium-strength high-plasticity Ti-Ta alloy

By adding oxygen elements to the Ti-Ta alloy and controlling the impurity content, a medium-strength high-plastic Ti-Ta alloy that is resistant to boiling and concentrated nitric acid corrosion was prepared, which solved the problem of insufficient corrosion performance of existing titanium alloys in boiling and concentrated nitric acid environment, and achieved the improvement of high tensile strength and yield strength, which was suitable for spent fuel after-treatment equipment.

CN119843105APending Publication Date: 2025-04-18XIAN RARE METAL MATERIALS RES INST CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510080760.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing titanium alloys have insufficient corrosion performance in boiling and concentrated nitric acid environments, and their structural strength and processability are poor, making it difficult to meet the needs of spent fuel after-treatment equipment.

Method used

By adding oxygen elements to the Ti-Ta alloy, oxygen microalloyation is formed, oxygen content and impurity content are controlled, and medium-strength high-plastic Ti-Ta alloy with high tensile strength and yield strength is prepared.

Benefits of technology

Without losing the corrosion performance and elongation of the alloy, the tensile strength and yield strength of the material are greatly improved, and are suitable for the construction of spent fuel post-treatment factories.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119843105A_ABST
    Figure CN119843105A_ABST
Patent Text Reader

Abstract

The invention discloses a medium-strength high-plasticity Ti-Ta alloy resistant to boiling concentrated nitric acid corrosion. The medium-strength high-plasticity Ti-Ta alloy is composed of, by mass, 5.5%-6.5% of Ta, 0.16%-0.6% of O and the balance Ti and inevitable impurities. In addition, the invention further discloses a preparation method of the Ti-Ta alloy, sponge titanium, Ti-Ta intermediate alloy scraps and titanium dioxide powder wrapping titanium foil are mixed and then smelted, and a mixture is obtained; and then rolling and annealing to obtain the Ti-Ta alloy. The alpha-type titanium alloy with a uniform structure and a single phase is obtained through oxygen microalloying, so that the alloy has excellent mechanical properties and nitric acid corrosion resistance and also has excellent welding performance and machinability, the alloy is simple in component, the preparation method is short in period and high in efficiency, the strong plasticity and the nitric acid corrosion resistance are synergistically improved, and the preparation method is suitable for industrial production. Basic data support and candidate materials are provided for reinforcement and corrosion prevention of metal structure materials for spent fuel aftertreatment equipment and design of new materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of Ti-Ta alloys and preparation methods thereof, and particularly relates to a medium-strength and high-plasticity Ti-Ta alloy resistant to boiling concentrated nitric acid corrosion and a preparation method thereof. Background Art

[0002] With the rapid increase in domestic nuclear power installed capacity, more and more spent nuclear fuel is unloaded from reactors and accumulated in temporary storage pools next to nuclear power plants. The pools of each power plant have become saturated and urgently need to be reprocessed. Reprocessing is an extremely complex radiochemical process, which is a chemical process in which nitric acid is used to dissolve the sheared fuel pellets, and then an extractant is used to remove nuclear fission products and recover uranium (U) and plutonium (Pu). The key equipment involved in this process, such as dissolvers and evaporators, is in high-concentration, high-radioactive boiling nitric acid for a long time. Ensuring the safe and reliable operation of the equipment is the primary goal. There have been many spent fuel leakage accidents caused by corrosion of equipment materials and insufficient structural strength in foreign reprocessing plants, which have caused serious damage to property and personnel safety. How to synergistically improve the mechanical properties and corrosion resistance of reprocessing materials has always been a difficult problem restricting the development of this field. At present, domestic and foreign researchers have developed and researched materials with high corrosion resistance in nitric acid environments, including stainless steel, titanium alloy and zirconium alloy. Stainless steel will experience intergranular corrosion in nitric acid solutions containing oxidizing ions, and zirconium alloy may be at risk of stress corrosion cracking in nitric acid solutions, so titanium alloy has become an ideal material for post-processing equipment.

[0003] Therefore, people are eager to obtain a titanium alloy that is resistant to boiling concentrated nitric acid corrosion and has certain structural strength and machinability. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a medium-strength and high-plasticity Ti-Ta alloy resistant to boiling concentrated nitric acid corrosion in view of the above-mentioned deficiencies in the prior art. The Ti-Ta alloy is based on the Ti-Ta alloy for post-processing, oxygen elements are added to form oxygen micro-alloying, and the tensile strength and yield strength of the material are greatly improved without losing the alloy's resistance to boiling concentrated nitric acid corrosion and elongation, providing a candidate material for the construction of a large spent fuel post-processing plant.

[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a medium-strength and high-plasticity Ti-Ta alloy resistant to corrosion by boiling concentrated nitric acid, characterized in that the Ti-Ta alloy is composed of the following components in mass fractions: Ta 5.5%~6.5%, O 0.16%~0.6%, and the remainder is Ti and unavoidable impurities.

[0006] The present invention is based on Ti-Ta alloy for post-processing, adds oxygen elements to form oxygen micro-alloying, and achieves a significant increase in the tensile strength and yield strength of the material without losing the alloy's corrosion resistance to boiling concentrated nitric acid and elongation, providing candidate materials for the construction of large-scale spent fuel post-processing plants.

[0007] The present invention controls the oxygen content to prevent the oxygen atoms from combining with titanium atoms to form oxides when the oxygen content exceeds 0.7wt.%. The interface between the oxides and the titanium metal matrix may become the source of cracks, or when subjected to external forces, these oxides may hinder the movement of dislocations, resulting in the material being more susceptible to brittle fracture.

[0008] The above-mentioned medium-strength and high-plasticity Ti-Ta alloy resistant to boiling concentrated nitric acid corrosion is characterized in that the unavoidable impurities include C, H and N, wherein the mass fraction of the impurities satisfies: C is not more than 0.03%, H is not more than 0.005%, and N is not more than 0.005%. The present invention prevents the corrosion performance of the material from deteriorating due to excessive impurity content by controlling the content of impurities, helps prevent intergranular corrosion by controlling the content of C, helps prevent stress corrosion cracking by controlling the content of N, and helps prevent hydrogen embrittlement by controlling the content of H.

[0009] In addition, the present invention provides a method for preparing a medium-strength and high-plasticity Ti-Ta alloy resistant to corrosion by boiling concentrated nitric acid, characterized in that the method comprises the following steps: Step 1: uniformly mix titanium sponge, Ti-Ta master alloy chips and titanium dioxide powder wrapped with titanium foil, and then smelt them to obtain a smelted ingot with a lamellar structure; Step 2: cutting the smelted ingot obtained in step 1, and then removing the surface oxide scale to obtain a billet; Step 3, heating and keeping the blank obtained in step 2, and then immediately rolling it to obtain a rolled plate; Step 4: vacuum annealing the rolled plate obtained in step 3 to obtain a medium-strength and high-plasticity Ti-Ta alloy resistant to boiling concentrated nitric acid corrosion.

[0010] The above method is characterized in that the mass purity of the titanium sponge in step 1 is not less than 99.7%; the mass purity of the titanium dioxide powder is not less than 97%. The present invention ensures the mass purity of the medium-strength and high-plasticity Ti-Ta alloy resistant to boiling concentrated nitric acid corrosion through the purity of the raw materials, and prevents the performance of the prepared material from being reduced due to excessive impurity content.

[0011] The above method is characterized in that the smelting process in step 1 is: placing the sample in a copper crucible in a vacuum smelting furnace, adjusting the electrode distance to 1mm to 3mm to start arcing, with a smelting current of 400A to 550A and a magnetic stirring current of 5A to 15A, and smelting is repeated 4 to 6 times. The present invention controls the smelting process and parameters to prepare a smelting ingot with a uniform lamellar structure without component segregation, thereby ensuring the performance of a medium-strength and high-plasticity Ti-Ta alloy resistant to boiling concentrated nitric acid corrosion.

[0012] The above method is characterized in that the cutting in step 2 is performed by an electric spark wire cutting machine, and the removal of the surface oxide scale is performed by sandpaper. The present invention obtains a rolled billet with uniform thickness by cutting with an electric spark wire cutting machine, and removes the surface oxide scale, that is, removes impurities by using sandpaper, thereby ensuring the purity of the medium-strength and high-plasticity Ti-Ta alloy resistant to boiling concentrated nitric acid corrosion.

[0013] The above method is characterized in that the heating and heat preservation in step 3 is carried out in a muffle furnace, the heating and heat preservation in step 3 is carried out in a muffle furnace, the heating temperature is 820°C to 880°C, the heat preservation time is H×2min, wherein H is the thickness of the billet, in mm. The present invention controls the heating temperature below the phase transition point of the Ti-Ta alloy by controlling the parameters of the heating and heat preservation, thereby ensuring the mechanical properties of the medium-strength and high-plasticity Ti-Ta alloy resistant to boiling concentrated nitric acid corrosion, and at the same time preventing the uneven heating of the billet caused by too short a heat preservation time, which causes cracking in the subsequent rolling process.

[0014] The above method is characterized in that the rolling process described in step 3 is: multiple passes of rolling are performed on a two-roll mill, the pressing amount of each pass is not more than 30%, and the total deformation is 30% to 80%. When the total deformation does not meet the requirements after rolling 2 passes, reheating is performed, and the reheating temperature is the same as the heating and heat preservation temperature in step 3, and the time is halved. The present invention optimizes the organizational structure of the medium-strength and high-plasticity Ti-Ta alloy resistant to boiling concentrated nitric acid corrosion by controlling the rolling parameters, achieves excellent mechanical properties, and prevents the material from cracking due to temperature reduction by reheating.

[0015] The above method is characterized in that the temperature of the vacuum annealing in step 4 is 500°C to 750°C and the time is 1h to 5h. The present invention adjusts the ratio of α phase and β phase in the medium-strength and high-plasticity Ti-Ta alloy resistant to boiling concentrated nitric acid corrosion by controlling the parameters of vacuum annealing, so that the medium-strength and high-plasticity Ti-Ta alloy resistant to boiling concentrated nitric acid corrosion has the best strength, toughness and plasticity.

[0016] The above method is characterized in that the room temperature tensile mechanical properties of the medium-strength and high-plasticity Ti-Ta alloy resistant to boiling concentrated nitric acid corrosion in step 4 meet the following requirements: yield strength is not less than 350MPa, tensile strength is not less than 450MPa, and elongation is not less than 25%; the medium-strength and high-plasticity Ti-Ta alloy resistant to boiling concentrated nitric acid corrosion has a corrosion rate of less than 0.1mm / y in nitric acid with a temperature of 298K~393K and a concentration of 1mol / L~14mol / L under a stress of 0.1MPa~10MPa.

[0017] Compared with the prior art, the present invention has the following advantages: 1. The present invention is based on Ti-Ta alloy for post-processing, and oxygen elements are added to form oxygen micro-alloying. Through the solid solution strengthening effect of the impurity oxygen element, the generation of a second phase in the material to cause a decrease in nitric acid corrosion resistance is avoided. Under the premise of not losing the alloy's boiling concentrated nitric acid corrosion resistance and elongation, the tensile strength and yield strength of the material are greatly improved, and the tensile strength is increased by 100%. At the same time, excellent welding performance and machinability are taken into account, providing candidate materials for the construction of a large spent fuel post-processing plant.

[0018] 2. The present invention prevents the corrosion performance of the material from deteriorating due to excessive impurity content by controlling the impurity content, helps prevent intergranular corrosion by controlling the C content, helps prevent stress corrosion cracking by controlling the N content, and helps prevent hydrogen embrittlement by controlling the H content.

[0019] 3. The room temperature tensile mechanical properties of the medium-strength and high-plasticity Ti-Ta alloy resistant to boiling concentrated nitric acid corrosion prepared by the present invention meet the following requirements: yield strength is not less than 350MPa, tensile strength is not less than 450MPa, and elongation is not less than 25%; the medium-strength and high-plasticity Ti-Ta alloy resistant to boiling concentrated nitric acid corrosion has a corrosion rate of less than 0.1mm / y in nitric acid with a temperature of 298K~393K and a concentration of 1mol / L~14mol / L under a stress of 0.1MPa~10MPa.

[0020] 4. The material designed by the present invention has simple composition, short preparation cycle, high efficiency, controllable process, short flow, simple process, and easy implementation, which synergistically improves the strength and plasticity of Ti-Ta alloy and its resistance to nitric acid corrosion. The application of this material involves chemical, biological, pharmaceutical, marine, energy and other fields.

[0021] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a low-magnification scanning electron microscope image of the Ti-Ta alloy prepared in Example 1 of the present invention.

[0023] Figure 2 It is a high-magnification scanning electron microscope image of the Ti-Ta alloy prepared in Example 1 of the present invention.

[0024] Figure 3 3 is the Ti element distribution diagram of the Ti-Ta alloy prepared in Example 1 of the present invention.

[0025] Figure 4 3 is the Ta element distribution diagram of the Ti-Ta alloy prepared in Example 1 of the present invention.

[0026] Figure 5 3 is the O element distribution diagram of the Ti-Ta alloy prepared in Example 1 of the present invention.

[0027] Figure 6 It is a stress-strain curve diagram of the Ti-Ta alloy prepared in Examples 2 to 5 of the present invention at room temperature.

[0028] Figure 7 It is a corrosion rate curve diagram of the Ti-Ta alloy prepared in Examples 2 to 5 of the present invention. DETAILED DESCRIPTION

[0029] Example 1 In this embodiment, the Ti-Ta alloy is composed of the following components in mass fractions: Ta 5.95%, O 0.35%, and the remainder is Ti and unavoidable impurities.

[0030] This embodiment includes the following steps: Step 1: Evenly mix titanium sponge with a mass purity of not less than 99.7%, Ti-Ta master alloy chips and titanium dioxide powder wrapped with titanium foil with a mass purity of not less than 97%, and then place them in a copper crucible in a vacuum melting furnace, adjust the electrode distance to 2 mm from the sample to start arcing, and repeatedly melt for 5 times with a melting current of 500A and a magnetic stirring current of 10A to obtain a smelted ingot with a lamellar structure; Step 2: Cut the smelted ingot obtained in step 1 by using an electric spark wire cutting machine, and then remove the surface oxide scale by using sandpaper to obtain a blank; Step 3, the blank obtained in step 2 is placed in a muffle furnace, heated and kept at a heating temperature of 860°C and a holding time of 16 minutes, and then immediately rolled on a two-roll mill for 2 passes, with the pressure of each pass not exceeding 30% and the deformation of 57%, and then returned to the furnace for heating at a heating temperature of 860°C and a holding time of 8 minutes, and then immediately rolled on a two-roll mill for 2 passes, with the pressure of each pass not exceeding 30%, so that the total deformation is 75%, to obtain a rolled plate; Step 4: vacuum anneal the rolled plate obtained in step 3 at 600° C. for 1 h to obtain a medium-strength and high-plasticity Ti-Ta alloy resistant to boiling concentrated nitric acid corrosion.

[0031] After testing, the mass fraction of C in the Ti-Ta alloy prepared in this embodiment is 0.02%, the mass fraction of H is 0.002%, the mass fraction of N is 0.003%, the yield strength at room temperature is 500 MPa, the tensile strength is 550 MPa, the elongation is 32%, and the corrosion rate in nitric acid with a concentration of 14 mol / L and a gas pressure of 10 MPa, at a temperature of 393 K, is 0.06 mm / y.

[0032] Figure 1 is a low-magnification scanning electron microscope image of the Ti-Ta alloy prepared in this embodiment, Figure 2 is a high-magnification scanning electron microscope image of the Ti-Ta alloy prepared in this embodiment. Figure 1 and Figure 2 It can be seen that the Ti-Ta alloy prepared in this embodiment presents an equiaxed structure, the grain size is about 25 μm, the structure is uniform and consistent, and there is no segregation.

[0033] Figure 3 is the Ti element distribution diagram of the Ti-Ta alloy prepared in this embodiment, Figure 4 is the Ta element distribution diagram of the Ti-Ta alloy prepared in this embodiment, Figure 5 is the O element distribution diagram of the Ti-Ta alloy prepared in this embodiment. Figure 3-Figure 5 It can be seen that the contents of the three elements Ti, Ta and O in the Ti-Ta alloy prepared in this embodiment are evenly distributed, and the structure is an equiaxed structure.

[0034] Example 2 The difference between this embodiment and embodiment 1 is that the Ti-Ta alloy is composed of the following components in mass fractions: Ta 5.82%, O 0.25%, and the balance Ti and unavoidable impurities.

[0035] Example 3 The difference between this embodiment and embodiment 1 is that the Ti-Ta alloy is composed of the following components in mass fractions: Ta 5.88%, O 0.38%, and the remainder is Ti and unavoidable impurities.

[0036] Example 4 The difference between this embodiment and embodiment 1 is that the Ti-Ta alloy is composed of the following components in mass fractions: Ta 5.79%, O 0.47%, and the balance being Ti and unavoidable impurities.

[0037] Example 5 The difference between this embodiment and embodiment 1 is that the Ti-Ta alloy is composed of the following components in mass fractions: Ta 5.91%, O 0.62%, and the remainder is Ti and unavoidable impurities.

[0038] Figure 6 is a stress-strain curve of the Ti-Ta alloy prepared in Examples 2 to 5 of the present invention at room temperature. Figure 6 It can be seen that the oxygen content of the Ti-Ta alloys prepared in Examples 2 to 5 gradually increases, and the yield strength and tensile strength of the prepared Ti-Ta alloys are significantly increased, while the elongation does not decrease.

[0039] Figure 7 is a corrosion rate curve of the Ti-Ta alloy prepared in Examples 2 to 5 of the present invention, wherein the corrosion conditions are: at a pressure of 5 MPa, a temperature of 393 K, a concentration of 6 mol / L nitric acid, from Figure 7 It can be seen that the corrosion rates of the Ti-Ta alloys prepared in Examples 2 to 5 after being corroded in a 6 mol / L boiling nitric acid solution for 240 h are all less than 0.1 mm / y.

[0040] Example 6 In this embodiment, the Ti-Ta alloy is composed of the following components in mass fractions: Ta 6.48%, O 0.41%, and the remainder is Ti and unavoidable impurities.

[0041] This embodiment includes the following steps: Step 1: Evenly mix titanium sponge with a purity of not less than 99.7%, Ti-Ta master alloy chips and titanium dioxide powder wrapped with titanium foil with a purity of not less than 97%, and then place them in a copper crucible in a vacuum melting furnace, adjust the electrode distance to 1 mm from the sample to start arcing, and repeat the melting for 6 times with a melting current of 550A and a magnetic stirring current of 5A to obtain a molten ingot with a lamellar structure; Step 2: Cut the smelted ingot obtained in step 1 by using an electric spark wire cutting machine, and then remove the surface oxide scale by using sandpaper to obtain a blank; Step 3, the blank obtained in step 2 is placed in a muffle furnace, heated and kept at a heating temperature of 820°C and a holding time of 32 minutes, and then immediately rolled on a two-roll mill for 2 passes, with the pressure of each pass not exceeding 30% and the deformation of 55%, and then returned to the furnace for heating at a heating temperature of 820°C and a holding time of 16 minutes, and then immediately rolled on a two-roll mill for 2 passes, with the pressure of each pass not exceeding 30%, so that the total deformation is 80%, to obtain a rolled plate; Step 4: vacuum anneal the rolled plate obtained in step 3 at 750° C. for 2 h to obtain a medium-strength and high-plasticity Ti-Ta alloy resistant to boiling concentrated nitric acid corrosion.

[0042] After testing, the mass fraction of C in the Ti-Ta alloy prepared in this embodiment is 0.02%, the mass fraction of H is 0.003%, the mass fraction of N is 0.004%, the yield strength at room temperature is 512 MPa, the tensile strength is 545 MPa, the elongation is 31%, and the corrosion rate after corrosion for 240 hours in nitric acid with a temperature of 298 K and a concentration of 7 mol / L under a gas pressure of 0.1 MPa is 0.03 mm / y.

[0043] Example 7 In this embodiment, the Ti-Ta alloy is composed of the following components in mass fractions: Ta 5.52%, O 0.16%, and the remainder is Ti and unavoidable impurities.

[0044] This embodiment includes the following steps: Step 1: Evenly mix titanium sponge with a purity of not less than 99.7%, Ti-Ta master alloy chips and titanium dioxide powder wrapped with titanium foil with a purity of not less than 97%, and then place them in a copper crucible in a vacuum melting furnace, adjust the electrode distance to 3 mm from the sample to start arcing, and melt the mixture 4 times with a melting current of 400 A and a magnetic stirring current of 15 A to obtain a molten ingot with a lamellar structure; Step 2: Cut the smelted ingot obtained in step 1 by using an electric spark wire cutting machine, and then remove the surface oxide scale by using sandpaper to obtain a blank; Step 3: Place the blank obtained in step 2 into a muffle furnace, heat and keep it at 880°C for 10 minutes, and then immediately roll it on a two-roll mill for one pass, with the pressing amount of each pass not exceeding 30% and the total deformation amount being 30%, to obtain a rolled plate; Step 4: vacuum anneal the rolled plate obtained in step 3 at 500° C. for 5 h to obtain a medium-strength and high-plasticity Ti-Ta alloy resistant to boiling concentrated nitric acid corrosion.

[0045] After testing, the mass fraction of C in the Ti-Ta alloy prepared in this embodiment is 0.01%, the mass fraction of H is 0.004%, the mass fraction of N is 0.003%, the yield strength at room temperature is 511 MPa, the tensile strength is 551 MPa, the elongation is 33%, and the corrosion rate is 0.01 mm / y after corrosion for 240 hours in nitric acid with a concentration of 1 mol / L and a gas pressure of 5 MPa at a temperature of 353 K.

[0046] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A medium-strength and high-plasticity Ti-Ta alloy resistant to corrosion by boiling concentrated nitric acid, characterized in that: The Ti-Ta alloy consists of the following components in mass fractions: Ta 5.5%-6.5%, O 0.16%-0.6%, and the balance Ti and inevitable impurities.

2. The medium-strength and high-plasticity Ti-Ta alloy resistant to corrosion by boiling concentrated nitric acid according to claim 1, characterized in that: The unavoidable impurities include C, H and N, wherein the mass fractions of the impurities satisfy: C is not greater than 0.03%, H is not greater than 0.005%, and N is not greater than 0.005%.

3. A method for preparing a medium-strength and high-plasticity Ti-Ta alloy resistant to boiling concentrated nitric acid corrosion as claimed in claim 1 or 2, characterized in that: The method comprises the following steps: Step 1: uniformly mix titanium sponge, Ti-Ta master alloy chips and titanium dioxide powder wrapped with titanium foil, and then smelt them to obtain a smelted ingot with a lamellar structure; Step 2: cutting the smelted ingot obtained in step 1, and then removing the surface oxide scale to obtain a billet; Step 3, heating and keeping the blank obtained in step 2, and then immediately rolling it to obtain a rolled plate; Step 4: vacuum annealing the rolled plate obtained in step 3 to obtain a medium-strength and high-plasticity Ti-Ta alloy resistant to boiling concentrated nitric acid corrosion.

4. The method according to claim 3, characterized in that: The mass purity of the titanium sponge in step 1 is not less than 99.7%; the mass purity of the titanium dioxide powder is not less than 97%.

5. The method according to claim 3, characterized in that: The smelting process described in step 1 is: placing it in a copper crucible in a vacuum melting furnace, adjusting the electrode distance from the sample to 1mm~3mm to start arcing, with a melting current of 400A~550A and a magnetic stirring current of 5A~15A, and repeating the melting 4~6 times.

6. The method according to claim 3, characterized in that The cutting in step 2 is performed by an electric spark wire cutting machine, and the removal of the surface oxide scale is performed by sandpaper.

7. The method according to claim 3, characterized in that The heating and heat preservation in step 3 is carried out in a muffle furnace, the heating temperature is 820°C~880°C, and the heat preservation time is H×2min, where H is the thickness of the blank, in mm.

8. The method according to claim 3, characterized in that The rolling process described in step three is: multiple rolling passes are performed on a two-roll rolling mill, the pressing amount in each pass is not more than 30%, and the total deformation is 30% to 80%. When the total deformation does not meet the requirements after rolling for 2 passes, the furnace is reheated. The furnace heating is the same as the heating and insulation temperature in step three, and the time is halved.

9. The method according to claim 3, characterized in that: The vacuum annealing in step 4 is performed at a temperature of 500° C. to 750° C. and for a time of 1 h to 5 h.

10. The method according to claim 3, characterized in that: The room temperature tensile mechanical properties of the medium-strength and high-plasticity Ti-Ta alloy resistant to boiling concentrated nitric acid corrosion in step 4 meet the following requirements: yield strength is not less than 350MPa, tensile strength is not less than 450MPa, and elongation is not less than 25%; the medium-strength and high-plasticity Ti-Ta alloy resistant to boiling concentrated nitric acid corrosion has a corrosion rate of less than 0.1mm / y in nitric acid with a concentration of 1mol / L~14mol / L and a gas pressure of 0.1MPa~10MPa, a temperature of 298K~393K, and a concentration of 1mol / L~14mol / L.

Citation Information

Cited By

  • High-toughness corrosion-resistant Ti-Zr-Ta alloy and preparation method thereof

    CN122038847A

  • High-toughness wear-resistant corrosion-resistant Ti-Zr-Ta plate and preparation method thereof

    CN122147135A